Application of the passive bioacoustic technique in the determination of some croaker species in the estuaries of Quang Ninh - Hai Phong - Pham, Van Chien; Nguyen, Van Quan; Nguyen, Cong Son; Pham, Van Tung; Nguyen, Duc The; Nguyen Thi, Kim Anh; Hin-Kiu, Mok (Vietnam Journal of Marine Science and Technology, 2021)
The passive bioacoustic technique has the principle of operation is to use underwater sound recording equipment, collecting the sound signals emitted by fish during the spawning season, analyze by software, through which it is possible to identify identified species name, population size, and the location of broodstock spawning in the study area. In this study, we used a combination of the passive bioacoustic method and analyzing the density of fish eggs and larvae of croaker species in the Tien Yen estuary (Quang Ninh province), Bach Dang estuary and Van Uc estuary (Hai Phong city) to identify spawning grounds of croaker in these areas. By analyzing samples of fish eggs, larvae, and acoustic signals of broodstock collected in August 2018 and September 2019, we identified four spawning grounds of croaker in the Tien Yen estuary, two spawning grounds of croaker in Bach Dang estuary and two in Van Uc estuary.